The Lost Sheep in Philosophy of Religion New Perspectives on Disability, Gender, Race, and Animals. - Hereth, Blake; Timpe, Kevin (Milton : Routledge, 2019)
Contemporary research in philosophy of religion is dominated by traditional problems such as the nature of evil, arguments against theism, issues of foreknowledge and freedom, the divine attributes, and religious pluralism. This volume instead focuses on unrepresented and underrepresented issues in the discipline. The essays address how issues like race, sexual orientation, gender identity, disability, feminist and pantheist conceptions of the divine, and nonhuman animals connect to existing issues in philosophy of religion. By staking out new avenues for future research, this book will be of interest to a wide range of scholars in analytic philosophy of religion and analytic philosophical theology.
14 Heavenly (Gendered) Bodies? Gender Persistence in the Resurrection and Its Implications15 Limbo, Hiddenness, and the Beatific Vision (and Procreation, for Some, in the Life to Come); 16 Religious Racial Formation Theory and Its Metaphysics: A Research Program in the Philosophy of Religion; Contributors; Index
Description based upon print version of record.
OCLC-licensed vendor bibliographic record.
Keywords: PHILOSOPHY / General; PHILOSOPHY / Religious; RELIGION / Philosophy; Religion -- Philosophy; Philosophical theology